Interface model-based configuration design of mechatronic systems for industrial manufacturing applications - Zheng, Chen; Qin, Xiansheng; Eynard, Benoît; Li, Jing; Bai, Jing; Zhang, Yicha; Gomes, Samuel (Robotics and computer-integrated manufacturing, 2019)
•Propose an interface model which provides designers with a common representation for the interfaces defined by designers from different disciplines.•Suggest the interface compatibility rules to help designers to check whether the alternatives of different modules integrate correctly.•Present an elimination algorithm based on the interface model and the interface compatibility rules to eliminate impossible alternative combinations.•Establish the design method for industrial mechatronic systems by integrating the elimination step into the configuration design process and provide designers with a high level guidance. Configuration design requires designers to develop a configuration by selecting and assembling from a subset of configurable modules according to customer requirements and engineering or physical constraints. In return, this does provide designers with a rapid and cost-efficient method to develop new products. However, unlike other applications, the number of alternative configurations from which designers can select the most suitable configuration is overly large owing to the vast number of multidisciplinary modules involved in industrial mechatronic systems. The paper proposes a configuration design method for mechatronic systems in the context of industrial manufacturing. For the large and complex mechatronic systems for manufacturing applications, with the support of the interface compatibility rules and the elimination algorithm in the configuration design method, the number of alternative combinations from which designers select the most suitable combination can be significantly reduced. The effectiveness and applicability of the proposed configuration design method is demonstrated with a robotic welding system.